Energy efficiency, cultural heritage values and the law conflicts and potential solutions. Issue 1 (October 2021) - Christiernsson, A; Geijer, M; Malafry, M
Abstract: The housing and service sector account for nearly 40 percent of the total energy usage in the European Union (EU). Improving energy efficiency in the building stock is therefore of vital importance to ensure climate goals. However, increasing the energy efficiency of existing buildings can lead to conflicts with other sustainability goals, such as the preservation of cultural heritage values of the built environment. How this conflict is handled in practice will depend on the design of the legislation and ultimately, the legal system. Not only is legislation on the protection of cultural values necessary, the legal system as a whole must be coherent and without deficits, loop-holes and conflicts contradicting goal fulfilment. Moreover, the norms must be effectively applied and complied with. Results of an interdisciplinary research project assessing the effectiveness of the Swedish legal system in reaching energy goals while preserving heritage values, show that meeting sustainability goals are jeopardized by not applying the law in accordance with the intent of the legislator. This paper elaborates on the deficits identified and how they can be improved in order to handle sustainability conflicts.